Differential transport of Influenza A neuraminidase signal anchor peptides to the plasma membrane - Ernst, Andreas M.; Zacherl, Sonja; Herrmann, Alexia; Hacke, Moritz; Nickel, Walter; Wieland, Felix T.; Brügger, Britta (FEBS letters, 2013)
Influenza A Neuraminidase is essential for virus release from the cell surface of host cells. Given differential structures of the N-terminal sequences including the transmembrane domains of neuraminidase subtypes, we investigated their contribution to transport and localization of subtypes N1, N2 and N8 to the plasma membrane. We generated consensus sequences from all protein entries available for these subtypes. We found that 40N-terminal the forty N-terminal amino acids are sufficient to confer plasma membrane localization of fusion proteins, albeit with different efficiencies. Strikingly, subtle differences in the primary structure of the part of the transmembrane domain that resides in the exoplasmic leaflet of the membrane have a major impact on transport efficiency, providing a potential target for the inhibition of virus release.